Appeals to Social Norms and Taxpayer Compliance. (20th June 2019) - Alm, James; Schulze, William D.; von Bose, Carrie; Yan, Jubo
Abstract : We use laboratory experiments to examine the impact of appeals to social norms on the compliance decisions of individuals. We test the effects of two main types of social norms: "descriptive norms, " or the type of behavior that is typical or most frequently enacted, and "injunctive norms, " or the type of behavior that "constitutes morally approved and disapproved conduct". In addition, for injunctive norms, we introduce approval‐framed and disapproval‐framed injunctive norm messages. Our results indicate that normative appeals generally have a modest and positive impact on tax compliance, if not always statistically significant. The magnitude of both approval‐ and disapproval‐framed injunctive norm messages is an increase of around 2% in reported taxes.